An Analysis of English Lexical Collocation Found in English Newspaper - Yulfi Yulfi; Sastika Seli; Reni Ariska (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study was conducted to find out the answer of question about what the English lexical collocation found in English Newspaper, The Jakarta Post. This study was designed as a descriptive qualitative research and data of the study was described in form of qualitative description. The data was taken from the headlines of the Jakarta post newspaper which published on April 4th - 9th 2016. The sources of the data in this study were sentences and utterances that contain collocation. Human instrument was the only instrument used in collecting and analyzing the data gathered. The result of this study showed that (1) there were fourty four English lexical collocations found in the Jakarta post newspaper and (2) the meanings of English lexical collocation were fourty three had denotative meaning and one had connotative meaning. Keywords: english lexical collocation, words meaning, the Jakarta post